2004
DOI: 10.4049/jimmunol.172.6.3876
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Developmental Endothelial Locus-1 in a Subset of Macrophages for Engulfment of Apoptotic Cells

Abstract: A major function of macrophages is to engulf apoptotic cells to prevent them from releasing noxious materials as they die. Milk fat globule-EGF-factor 8 (MFG-E8) is a glycoprotein secreted by activated macrophages that works as a bridge between apoptotic cells and phagocytes by specifically recognizing phosphatidylserine exposed on apoptotic cells. In this study, we found that developmental endothelial locus-1 (Del-1), originally identified as an embryonic endothelial cell protein that binds αvβ3 integrin, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
117
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 50 publications
5
117
1
Order By: Relevance
“…When we stimulated differentiated THP-1 macrophages with Dex in vitro, we observed a dose-dependent induction of MFG-E8 expression on mRNA, as well as on protein level (Figure 1c). No such effect was seen with the close MFG-E8 relative developmental endothelial locus-1 (Del-1) 21 or the known GCinducible gene annexin A1 (Anx A1). 22 Interestingly, the majority of MFG-E8 remained associated with the macrophages as confirmed by ELISA measurements of cellular lysates and cell-free culture supernatants (Figure 1e).…”
Section: Resultsmentioning
confidence: 99%
“…When we stimulated differentiated THP-1 macrophages with Dex in vitro, we observed a dose-dependent induction of MFG-E8 expression on mRNA, as well as on protein level (Figure 1c). No such effect was seen with the close MFG-E8 relative developmental endothelial locus-1 (Del-1) 21 or the known GCinducible gene annexin A1 (Anx A1). 22 Interestingly, the majority of MFG-E8 remained associated with the macrophages as confirmed by ELISA measurements of cellular lysates and cell-free culture supernatants (Figure 1e).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that milk fat globule EGF 8 (MFG-E8) is an essential factor for the clearance of apoptotic B cells in the spleen and MFG-E8-deficient mice suffer from autoimmunity [19]. Interestingly, apoptotic thymocytes are normally cleared in MFG-E8-deficient mice and MFG-E8 is not expressed in thymic macrophages [23]. In contrast, the clearance of apoptotic cells in mice lacking the Mer receptor tyrosine kinase was severely impaired following the induction of thymocytes apoptosis by Dex, while apoptotic thymocytes were not accumulated in the thymus without Dex challenge [13,24,25].…”
Section: Defective Clearance Of Apoptotic Thymocytes May Trigger Automentioning
confidence: 99%
“…Mouse MFG EGF factor 8 (MFG-E8), called lactadherin in humans, is a 72-kDa glycoprotein secreted from mammary epithelial cells, macrophages, and immature dendritic cells (12)(13)(14)(15). We recently showed that MFG-E8 specifically binds to apoptotic cells by recognizing phosphatidylserine (PS) exposed on the surface of the apoptotic cells and promotes the engulfment of apoptotic cells by phagocytes (12).…”
mentioning
confidence: 99%